The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1038/gt.2008.185
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous transferrin, RGD peptide and dual-targeted nanoparticles enhance anti-VEGF intraceptor gene delivery to laser-induced CNV

Abstract: Choroidal neovascularization (CNV) leads to loss of vision in age-related macular degeneration (AMD), the leading cause of blindness in adult population over 50 years old. In this study, we developed intravenously administered, nanoparticulate, targeted nonviral retinal gene delivery systems for the management of CNV. CNV was induced in Brown Norway rats using a 532 nm laser. We engineered transferrin, arginine-glycineaspartic acid (RGD) peptide or dual-functionalized poly-(lactideco-glycolide) nanoparticles t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
142
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(143 citation statements)
references
References 48 publications
1
142
0
Order By: Relevance
“…37,38 Biodegradation and ocular tissue reaction to microspheres or NPs of poly (D, L-lactide) or PLGA have been studied earlier in vitro 39,40 and in vivo. [41][42][43][44] In this study, we showed the inhibitory efficiency of shRNA-expressing plasmid DNA (pDNA) targeting HIF1a (pshHIF-1a) on laser-induced CNV in rats, and further evaluated the therapeutic potential of PLGA NPs as a non-viral vector for pshHIF-1a gene transfection to the posterior segment of eyes.…”
Section: Introductionmentioning
confidence: 99%
“…37,38 Biodegradation and ocular tissue reaction to microspheres or NPs of poly (D, L-lactide) or PLGA have been studied earlier in vitro 39,40 and in vivo. [41][42][43][44] In this study, we showed the inhibitory efficiency of shRNA-expressing plasmid DNA (pDNA) targeting HIF1a (pshHIF-1a) on laser-induced CNV in rats, and further evaluated the therapeutic potential of PLGA NPs as a non-viral vector for pshHIF-1a gene transfection to the posterior segment of eyes.…”
Section: Introductionmentioning
confidence: 99%
“…29 However, previous studies have usually prepared the nanoparticles first, and then added a targeting molecule for conjugation on the surface of the nanoparticle. 17,29,30 This method is limited by the difficulty in controlling the number of targeting moieties conjugated to the constructed nanoparticles. In this report, synthesis of the ligand-conjugated lipid, DSPE-PEG-RGD, was performed by Michael addition reactions between activated maleimide and thiol groups prior to preparation of the liposomes ( Figure 1A).…”
mentioning
confidence: 99%
“…Most research has focused on the specific targeting of cells expressing disease-associated biomarkers, as in the case of cancer. Various moieties have been examined as targeting agents, including vitamins, [24] carbohydrates, [25] aptamers, [26] peptides (e.g., Arg-Gly-Asp, allatostatin, transactivating transcriptional activator) [27][28][29] and proteins (e.g., lectins, and transferrin) [30][31] However, active agents, such as ligands for the receptors and antibodies to the surface proteins have been used extensively to target specific cells, the majority of research to date has focused on antibodies.…”
Section: Particle Class Materials Applicationmentioning
confidence: 99%